Use of personal reflexive modelling in challenging conceptualisations of cultural heritage - Gibbons, Leisa (Taylor Francis, 2017)
Group Conceptual and theoretical modelling has been deployed in archival science for over 20 years to critically examine the complex and diverse roles that records and archives play at individual, community and societal levels. However, how theoretical models can be utilised by professionals in practice has not, in general, been adequately described or explained. Added to this, the growing discourse on identifying and examining power structures inherent in institutional practices and policies, adds pressure to an increasingly complex heritage environment. A recent call for activist archivists is engaging, but lacks robust communication of the tools, methods and frameworks that can initiate and support how activism is deployed, evaluated and evolved, and what impact activism has as a transformative practice. This paper proposes the use of a theoretical model, the Mediated Recordkeeping Model (MRkM), as a framework to guide the development and implementation of self-reflexive modelling processes to challenge individual assumptions and practices within the memory and heritage professions. The reflexive modelling process is explored via a use case. Future research in this area would look towards building and testing formal methods that deploy the reflexive modelling technique and use of the MRkM.